BZR1 Regulates Brassinosteroid-Mediated Activation of AMT1;2 in Rice - Yang, Shuo; Yuan, Depeng; Zhang, Yang; Sun, Qian; Xuan, Yuan Hu (Frontiers in Plant Science, 2021)
Although it is known that brassinosteroids (BRs) play pleiotropic roles in plant growth and development, their roles in plant nutrient uptake remain unknown. Here, we hypothesized that BRs directly regulate ammonium uptake by activating the expression of rice AMT1-type genes. Exogenous BR treatment upregulated both AMT1;1 and AMT1;2 expression, while this induction was impaired in the BR-receptor gene BRI1 mutant d61-1. We then focused on brassinazole-resistant 1 (BZR1), a central hub of the BR signaling pathway, demonstrating the important role of this signaling pathway in regulating AMT1 expression and rice roots NH4+ uptake. The results showed that BR-induced expression of AMT1;2 was suppressed in BZR1 RNAi plants but was increased in bzr1-D, a gain-of-function BZR1 mutant. Further EMSA and ChIP analyses showed that BZR1 bound directly to the BRRE motif located in the promoter region of AMT1;2. Moreover, cellular ammonium contents, 15NH4+ uptake, and the regulatory effect of methyl-ammonium on root growth are strongly dependent on the levels of BZR1. Overexpression lines of BRI1 and BZR1 and Genetic combination of them mutants showed that BZR1 activates AMT1;2 expression downstream of BRI1. In conclusion, the findings suggest that BRs regulation of NH4+ uptake in rice involves transcription regulation of ammonium transporters.